Understanding the Strength of Gentleness: Soft-Skilled Leadership on the Rise - Marques, Joan (Journal of business ethics, 2013)
This paper focuses on the topic of “soft skills” as an intrinsic part of successful leadership. The first part of the paper presents a literature review about the shift in perspective in recent years on what matters in leadership, and the significant changes this prompted in some areas of education and corporate recruitment. In the second part, the findings of a year round study conducted among Los Angeles based workforce members in an MBA program are presented. By utilizing a multi-method approach, consisting of a survey model with three open ended, interview style questions, and data analysis in phenomenological trend, a number of interesting findings emerged, supporting the literature reviewed, that soft leadership skills, such as self-awareness, self-regulation, motivation, empathy, and social skills, are steadily on the rise, and that greater attention should be apportioned to strengthen these skills in future leaders.